Investor Origin and Deforestation: Evidence from Global Mining Sites - Xie, Victoria Wenxin; You, Wei; Goldblatt, Ran (The Review of Economics and Statistics, 2025)
Abstract Does mining activity lead to deforestation? How does investor origin affect the environmental impacts of mining operations? We investigate these questions by estimating the causal impact of mineral price changes on deforestation near mining sites. Combining global mine propertylevel data with high-resolution satellite imagery on forest cover, we find a positive elasticity of deforestation to mineral price shocks. This elasticity is significantly lower when mine owners are from countries with higher income or better institutions, but it is not affected by host country characteristics. Evidence suggests that mine owners from higher-income countries induce different types of local economic activity.